Delayed Presentation of Air-Leak Features Following Low-impact Blunt Neck Trauma in a Child - Samreen Yusuf; Anil Kumar Goel; T.P Murugan (Indian Pediatrics Case Reports)
Background: Tracheobronchial injury is a potentially fatal condition that can occur following a blunt or penetrating trauma. Due to anatomical characteristics in children, such injuries are rarely seen in this age group. Clinical Description: An 8-year-old boy presented with increasing breathing difficulty and chest pain, 32 hours after sustaining a low-impact blunt-neck trauma by the handle-bar of the bicycle. On examination, he was neurologically and hemodynamically stable with increased work of breathing. There was subcutaneous emphysema extending from the anterior neck to below the infraclavicular region, with overlying ecchymosis over the neck. Management and Outcome: After initial stabilization, an ultrasound revealed a break in the air-mucosal interphase at the level of the supraglottic airway/trachea; chest X-ray showed subcutaneous emphysema (SE) in the cervicofacial, thoracic, and bilateral axillary regions, whereas computed tomography (CT) revealed pneumomediastinum along with SE. Conservative management with supportive care and close monitoring helped in a successful recovery. Conclusion: Minor, low-impact, blunt neck trauma in children may appear deceptively benign but may present late with air-leak features due to underlying laryngeal injury. The case reiterates the importance of thorough evaluation with radiographic imaging including CT in such children with blunt neck trauma.